Budaya Carok Masyarakat Madura dalam Perspektif Hukum Pidana Islam - Syaputra, Muhamad Ilham; Ishaq, Ishaq (IAIN Langsa, 2024)
Ideally, conflicts are resolved through legal channels that uphold justice. However, in reality, the Madurese community often resorts to the tradition of carok, particularly in cases involving honor, which frequently result in fatalities. This raises legal issues, especially regarding criminal accountability for carok perpetrators under both state law and Islamic law. This study aims to analyze the carok tradition, which leads to death, from the perspective of Islamic criminal law, including criminal accountability, the application of Islamic law to carok, and specific conditions where carok is committed out of necessity or self-defense. This article is a library-based study with a juridical-normative approach. The methodology employed is descriptive-analytical. The findings reveal that carok perpetrators are criminally responsible for their actions that cause death. In Islamic law, carok is categorized as an act of murder with specific sanctions, except when it is carried out in self-defense or in defense of one's family.